El partido socialista de Chile en dictadura Clandestinidad, exilio, ruptura y unificación - Muñoz Tamayo, Víctor (Docta Ignorancia, 2022)
This text focuses on the PS during the 17 years of dictatorship that followed the coup that violently ended the Popular Unity government. The Pinochet regime subjected the PS to the traumatic task of recomposing itself in the midst of extreme repression, clandestinity, the exile diaspora and the intense debate around the causes of the defeat, the alternatives of the anti-dictatorial struggle and the possibilities and paths of a socialist project in Chile. The period is long and contains both continuities and deep transformations in Chilean socialism, which we have arranged, for analytical purposes, in three moments or cycles. Each cycle is characterized by being centered on certain debates and conditioning factors that determine the partisan dynamics of the organic socialists. The very historical development of each cycle implies its overcoming and the passage to another cycle with different distinctive characteristics.